2022
DOI: 10.1111/ijcs.12844
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities of brand corporate social responsibility classification: A review, new conceptualization and future research agenda

Abstract: Scholars have outlined several corporate social responsibility (CSR) classifications to analyse the wide range of CSR initiatives. The usage of diverse CSR types has resulted in independent and fragmented research. Previous literature reviews have analysed the overall CSR domain or focused on specific CSR activity, like cause‐related marketing. A comprehensive review of CSR classifications is not available to the best of the authors' knowledge. This article synthesizes the literature on CSR classification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 263 publications
1
8
0
Order By: Relevance
“…Next, given that the objective of this research was to identify and measure consumer responses to the CSR types employed during the COVID‐19 pandemic, the authors used an inductive approach to identify and classify CSR types versus a deductive approach using existing frameworks from past research (e.g., Bower & Grau, 2009; Green & Peloza, 2015; Mishra & Modi, 2016; Prasad & Kumar, 2022). That said, the authors found the three broad categories of CSR proposed by Peloza and Shang (2011) useful for organizing their nine CSR types (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, given that the objective of this research was to identify and measure consumer responses to the CSR types employed during the COVID‐19 pandemic, the authors used an inductive approach to identify and classify CSR types versus a deductive approach using existing frameworks from past research (e.g., Bower & Grau, 2009; Green & Peloza, 2015; Mishra & Modi, 2016; Prasad & Kumar, 2022). That said, the authors found the three broad categories of CSR proposed by Peloza and Shang (2011) useful for organizing their nine CSR types (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, to enhance experimental control and keep the research design more manageable, this research featured fictitious firms and only included information about starting versus stopping CSR during the COVID-19 pandemic. Future research could investigate how consumers respond to actual firms, firms that engage in past or ongoing CSR in addition to starting versus stopping CSR in response to a crisis or disaster, or firms that switch to different CSR types over the course of a crisis or disaster.Related, future research could explore the effects of engaging in more than one CSR type at a time(Prasad & Kumar, 2022) in response to a crisis or disaster. Recall that 22% of the 200 firms the authors reviewed engaged in more than one CSR type.…”
mentioning
confidence: 99%
“…Sharma, 2021), "social responsibility" (e.g. Prasad and Kumar, 2022) or "ethical consum à " (e.g. Groening et al, 2018).…”
Section: Identification Of Sourcesmentioning
confidence: 99%
“…Given the impacts of sustainability on business, some studies summarized the current knowledge base on specific subthemes related to brand equity and corporate social responsibility (CSR) (Ishaq and Di Maria, 2020; Prasad and Kumar, 2022), but the overlap between sustainability and branding workstreams is not addressed. They are anchored on domain-based perspectives, not incorporating a holistic perspective (Veloutsou et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The first direction examines the features of CTR. Some scholars have argued that CTR involves firms' engagement in technological innovation with the main purpose of benefitting their stakeholders rather than achieving economic profits (García-Piqueres and García-Ramos, 2022; Halme and Laurila, 2009;Prasad and Kumar, 2022). In CTR, meeting stakeholder demands is a starting point for developing new products or technologies; thus, CTR usually expands the core business or develops new businesses (Adomako and Nguyen, 2023;Halme and Laurila, 2009;Tesfaye and Fougère, 2021).…”
mentioning
confidence: 99%